Infância, construções de identidade e questões étino-raciais em a obra Negrinha - BRITO, Carla Ruane Rodrigues de (2023)
This article focuses on the construction of ethnic and cultural identity of childhood in Brazil, addressed in the work "Negrinha '' by Monteiro Lobato. Through bibliographical consultations and comparativism, we sought to understand Lobato's point of view on the personification of the childhood of white and black girls among characters in the work Negrinha. The foundations of this research of the childhood journey in history; identity, ethnicity. In this scope, the analyses resulted in the understanding of the personification of black and white childhood, where the invisibility of black children and the valorization of white childhood is observed, where the privilege and sense of superiority of an ethnical group prevails.